The Prophetic Method of Establishing Internal Peace in the State of Medinah: ریاست مدینہ میں داخلی امن کے قیام کا نبوی طریقہ کار - Majid, Abdul; Ahmed, Dr. Munir (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
Prophet’s biography and teachings are extremely important in the training and reform of individuals, society and nations. In terms of training, his sayings, deeds and silent approvals have equal status. However, there are some parts of his teachings that researchers have not paid enough attention to so far. They have been described briefly. Among these are his comprehensive measures for establishing internal peace at the state level. In the light of these, both individuals and society can adopt such protective measures through which human society can be at peace and harmony. It is known that when the Prophet Muhammad (PBUH) began preaching Islam, the number of Muslims was small. Moreover, Islam introduced a code of life that completely changed the conditions of the Arabian Peninsula at that time. The Prophet (PBUH) was fully prepared to face the problems and hardships that could arise as a result of this great mission. His enemies had more political, economic and military power, yet he took such steps that, despite the lack of economic and military resources, Islam got a full opportunity to flourish and flourish in the land of Arabia. Keeping this aspect in mind, We have tried to find an answer to the question: "What important steps did the Prophet Muhammad (PBUH) take to establish internal peace in the state of Medina after the migration to Medina?". The article presents various aspects of the Prophet’s (PBUH) Madani life to answer this question. Instead of going into details about these aspects, it has only focused on those points that are directly related to inner peace.